Pemerolehan Kosakata Bahasa Indonesia pada Anak Usia 4 Tahun di Desa Singkil - Rahmawati, Finka; Sabardila, Atiqa (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
The study of children's language processing is always intriguing. The purpose of this study is to identify and analyze the vocabulary processing abilities of 4-year-old children in Singkil Village, Indonesia. This qualitative case study involved 10 deliberately selected participants who were 4 years old. The data collected for this study included basic vocabulary such as verbs, nouns, adjectives, conjunctions, adverbials, pronominals, prepositions, numerals, and interjections. Notes and interviews were the data collection techniques used in this research. The analysis method employed in this study was the commensurate method, which included the use of the speech organ sorting technique. This variation in understanding highlights the individualized nature of language acquisition among preschool-aged children. The findings revealed that the most mastered word types were verbs (153 words), pronominal words (86 words), adjectives (70 words), nouns (63 words), conjunctions (58 words), adverbials (44 words), numerals (27 words), prepositions (13 words), and interjections (12 words). Therefore, it can be concluded that the acquisition of Indonesian vocabulary in 4-year-old children in Singkil Village, Sukoharjo Regency, is still categorized as underdeveloped (BB), as the process of acquiring Indonesian vocabulary in these children occurs naturally through daily activities.Key words: Indonesian language skills, vocabulary development, 4 year old children